Analysis Quality of Financial Reports of Regional Device Organizations in Manggarai Regional Governments - Aloisius Hama; Maxion Sumantak; Norman Duma Sitinjak (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to analyze the effect of the competence of financial management officials, regulations and the role of internal audit, with organizational commitment as a moderating variable on the quality of the financial reports of Regional Apparatus Organizations in the Manggarai Regency Government. The type of research used is causality research. The population in this study amounted to 99 employee, Manggarai Regency Apparatus Organizations that operate 33 respondent. The sample method is the census method, so that the entire population is used as a research sample. Hypothesis testing using multiple regression analysis and residual test with the help of the SPSS program. The results prove that the competence of management, regulatory and internal audit officials has a significant effect on the quality of financial reports simultaneously. Financial management and regulatory officials have a significant effect on the quality of financial reports, role of internal audit has no effect on the quality of financial reports. Organizational commitment as a moderating variable can moderate the relationship between the competence of financial management officials, regulations and the role of internal audit, with the quality of the financial reports of Local Government Organizations in the Manggarai Regency Government.